Role of Platinum Deposited on TiO2 in Photocatalytic Methanol Oxidation and Dehydrogenation Reactions - Luma M. Ahmed; Irina Ivanova; Falah H. Hussein; Detlef W. Bahnemann (International Journal of Photoenergy)
Titania modified nanoparticles have been prepared by the photodeposition method employing platinum particles on the commercially available titanium dioxide (Hombikat UV 100). The properties of the prepared photocatalysts were investigated by means of the Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), atomic force microscopy (AFM), and UV-visible diffuse spectrophotometry (UV-Vis). XRD was employed to determine the crystallographic phase and particle size of both bare and platinised titanium dioxide. The results indicated that the particle size was decreased with the increasing of platinum loading. AFM analysis showed that one particle consists of about 9 to 11 crystals. UV-vis absorbance analysis showed that the absorption edge shifted to longer wavelength for 0.5% Pt loading compared with bare titanium dioxide. The photocatalytic activity of pure and Pt-loaded TiO2 was investigated employing the photocatalytic oxidation and dehydrogenation of methanol. The results of the photocatalytic activity indicate that the platinized titanium dioxide samples are always more active than the corresponding bare TiO2 for both methanol oxidation and dehydrogenation processes. The loading with various platinum amounts resulted in a significant improvement of the photocatalytic activity of TiO2. This beneficial effect was attributed to an increased separation of the photogenerated electron-hole charge carriers.